Development of entry location assessment criteria (ELAC) model for Malaysian construction firms in international markets / Norizzati Ibrahim ... [et al.] - Ibrahim, Norizzati; Mat Isa, Che Maznah; Christopher Nigel, Preece; Mustaffa, Nur Kamaliah; Zainuddin, Atiqah Najwa (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Malaysian construction firms have increasingly gained investment opportunities in foreign countries pushed by the competitive and saturated domestic market. However, the entry location decision involves complex factors to be considered by these firms prior to their international operations. Currently, based on a secondary data obtained from the Construction Industry Development Board (CIDB) Malaysia, there are twelve (12) firms that are actively operating in international markets. The main objective of this preliminary study is to develop an entry location assessment criteria (ELAC) model based on the performance of Malaysian construction firms in international markets. The ELAC formula was derived through a development of taxonomy criteria from previous studies. The construction firms' performance was analyzed and ranked using a weightage score characterized under three (3) dimensions of country with the taxonomy criteria. First dimension involves entry location decision to countries in ASEAN, Non-ASEAN and both regions, while the second dimension involves entry location decision to ASEAN, Asia, Africa, United States of America and Europe while the third dimension involves entry location decision to countries categorized as Developing Countries (DLC); Least Developed Country (LDC); Newly Industrialized Countries (NIC); Developed Countries (DC); and Highly Developed Countries (HDC). The ELAC score shows that three (3) construction firms which are, Sapura Energy Berhad (66%), Gamuda Berhad (53%) and Sime Darby Berhad (50%) have sustained international operations in various locations by obtaining an ELAC score of more than 50% by venturing to ASEAN countries, developing countries and developed countries. Even though his study is limited to Malaysian construction firms, it provides significant information and contributes to the current knowledge in international market expansion. This ELAC model is useful especially for construction firms that are just beginning to explore foreign business opportunities or for the global players that are expanding geographically to new international markets.